Enforcing international law norms against terrorism - Bianchi, Andrea (Studies in international law, 2004)
State sponsors of terrorism : issues of international responsibility / Pierre-Marie Dupuy -- The legality of covert operations against terrorism in foreign states / Natalino Ronzitti -- The war against terrorism and jus in bello : are the Geneva Conventions out of date? / Luigi Condorelli and Yasmin Naqvi -- The treatment of terrorist suspects captured abroad : human rights and humanitarian law / Silvia Borelli -- Arresting terrorism : criminal jurisdiction and international relations / Madeline Morris -- The UN Security Council and international terrorism / Bardo Fassbender -- Countering catastrophic terrorism : an American view / Ruth Wedgwood -- The action of the European Union to combat international terrorism / August Reinisch -- Fighting against international terrorism : the Latin American response / Michelangela Scalabrino -- Terrorism as an international crime / Antonio Cassese -- The exercise of criminal jurisdiction over international terrorism / Robert Kolb -- Terrorism, national measures, and international supervision / Andrew Clapham -- National courts and the 'War on Terrorism' / Eyal Benvenisti -- The rendition of terrorist suspects to the United States : human rights and the limits of international cooperation / Silvia Borelli -- Freezing the assets of international terrorist organisations / Luca G. Radicati de Brozolo and Mauro Megliani -- The fight against the financing of terrorism between judicial and regulatory cooperation / Anna Gardella -- The Internet and terrorist activities / Ugo Draetta -- Cyberterrorism : a new challenge for international law / Richard Garnett and Paul Clarke -- Enforcing international law norms against terrorism : achievements and prospects / Andrea Bianchi.